Evaluation of Single Cross Maize Hybrids for Yield and Agronomical Advantage - Dhakal, Krishna Hari (Agronomy Journal of Nepal, 2025)
Grain yield for the maize genotypes is an important goal in maize breeding programs. The objective of this study was to evaluate the single cross maize hybrids for growth, yield, and traits associated with yield. Maize hybrids, RH-14 and RH-16 as standard checks, RAJKUMAR, JKMH502 and TX369 as commercial checks and CAH1511 and RH-10 as local checks variety along with other 112 single cross maize hybrids were evaluated in alpha lattice design with two replications at research field of National Maize Research Program (NMRP), Rampur, Chitwan, Nepal from November, 2022 to April, 2023. Agro-morphological and phenology based traits, yield and yield attributing traits as well as husk cover, lodging, stay green and disease were evaluated. Analysis of variance revealed that the significant differences among the tested genotypes for most of the traits that indicated the presence of genotypic differences. In present study, among all evaluated genotypes, RML142/CML581 produced the highest grain yield of 11373 kg ha⁻¹ and showed economic heterosis of 11.59% followed by commercial check JKMH502 (10191 kg ha⁻¹). Correlation revealed that grain yield had a positive and highly significant relation with number of ear ha⁻¹ (r= 0.796**), plant height (r= 0.401**), ear height (r=0.411**) and ear position (r=0.275**). The variability shown by the different genotypes can be used for the evaluation of high yielding and better performing variety. The study illustrated the existence of wide ranges of variation for most of the traits. Hence, selection of hybrids based on key traits performance would be of great importance in maize breeding research.